2010
DOI: 10.3109/08923971003690041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 14-kDa and 47-kDa protein molecules of age garlic extract on peritoneal macrophages

Abstract: according to our finding, 14-kDa and 47-kDa fractions of aged garlic extract are able to suppress NO production from macrophages, which can be used as a biological advantage. These molecules had no cytotoxic effect on macrophages and do not increase tumoricidal property of macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The anti-inflammatory activity of garlic 14-kDa protein has been previously reported in vitro 23 . The earlier findings suggested that protein exerted antiinflammatory effect in peritoneal macrophages by a remarkable reduction of NO production at a concentration range of 5-20 mg/ml.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The anti-inflammatory activity of garlic 14-kDa protein has been previously reported in vitro 23 . The earlier findings suggested that protein exerted antiinflammatory effect in peritoneal macrophages by a remarkable reduction of NO production at a concentration range of 5-20 mg/ml.…”
Section: Discussionmentioning
confidence: 95%
“…Isolation of 14-kDa protein from aged garlic extract Aqueous extract was prepared from dry garlic bulbs (AGE) by a method described previously [19][20][21][22][23] . Briefly, garlic bulbs were homogenized with distilled water in a blender.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effects of garlic extract against MeHg-induced leucocyte damage were related to the removal of oxidant species generated in the presence of MeHg due to the antioxidant effi cacy of garlic constituents. 14-kDa and 47-kDa protein molecules of aged garlic extract were able to suppress NO production from peritoneal macrophages (Daneshmandi et al 2011 ). These molecules had no cytotoxic effect on macrophages and did not increase tumouricidal property of macrophages.…”
Section: Immunomodulatory/ Haemagglutination Activitymentioning
confidence: 91%
“…These molecules had no cytotoxic effect on macrophages and did not increase tumouricidal property of macrophages. 14-kDa and 47-kDa protein molecules of aged garlic extract were able to suppress NO production from peritoneal macrophages (Daneshmandi et al 2011 ). These molecules had no cytotoxic effect on macrophages and did not increase tumouricidal property of macrophages.…”
Section: Immunomodulatory/ Haemagglutination Activitymentioning
confidence: 91%